MAKNA GERAK TORTOR MANGONDAS DALAM UPACARA KEMATIAN SAUR MATUA PADA MASYARAKAT BATAK TOBA DI KABUPATEN SAMOSIR - Rinda Turnip (Gesture: Jurnal Seni Tari, 2016)
Tortor Mangondas is an expression of sorrow that was created to meet the needsof indigenous meaningful honor the dead (and of the spirit / tondi man and tondithe first death) and is a communication between the real world and the other world(deceased) for application of this world can be given to the fathers and good luck /blessing of them can be given to people who live mainly heirs.This study aims tofind out what the meaning contained in Tortor Mangondas in Toba Batak society.The theoretical foundation of this research uses one theory, the theory of meaningand understanding tortor mangondas and death ceremonies.Location and time the research was conducted in Samosir and time for twomonths, the sample population figures there are some dancers and artists as wellas traditional leaders. The author conducted field observations, with videocapture, documentation, and conduct interviews with sources, as well as completethe data through research at the Village Siopat bill SamosirThe results based on the data that has been collected can be seen that TortorMangondas never appears solely as a form of dance in any society. But themotion-motion can still be explained the meaning of each movement performed.Tortor Mangondas created because someone who has died Saur matua not have achance to talk to the family to deliver the parting words and all expressions heartscontent. The social value as a society Batak Toba Mate Saur Matua wherebyTortor Mangondashasuhutan held with the objective of respect for parents and atthe same time submit a request to Mulajadi Nabolon prayer.